Growing Together as Professionals - Sarah Hudelson (Asociación Colombiana de Profesores de Ingles, 2016)
When conference organizer Lin Yai Shem sent me the conference theme Beyond Language Teaching: Growing Together, I began immediately to think of a focus of some of my recent work: teachers' professional development. In a profession as demanding as teaching, opportunities for professional development and renewal are crucial if we are to meet the challenges of helping ourselves and our students grow, not only linguistically, but also socially, emotionally, and intellectually. The term professional development means different things to different people, so I would like to begin by thinking about some of the meanings attached to the term.